Management of Liver Affections with the Anti Psoric Trios of Remedies (Homoeopathy for All, 2022)
Background: Hahnemann held that  all non venereal chronic diseases  are Psoric. That includes most  diseases of a chronic nature, all  skin diseases, most mental illness  other than syphilitic ones, allergies,  varicose veins, haemorrhoids, most  dysfunctional diseases of organs and  systems, etc. Chief Psoric remedies  he suggests include Sulphur,  Natrum mur, Calc carb, Arsenic  alb, Lycopodium, Petroleum, Silica,  Zinc amongst many others.1
Keywords: diseases; venereal chronic